Experimental investigation of properties and aging behavior of pineapple and sisal leaf hybrid fiber-reinforced polymer composites - Deeban Booramurthy; Maniraj Jaganathan; Ramesh Manickam (e-Polymers, 2023)
Using plant leaf fibers as reinforcements in thermo-plastic resins to produce affordable and lightweight composites is the subject of growing interest in research. Although these fibers have several advantages over synthetic fibers, mechanical characteristics of composites such as moisture absorption, poor wettability, and insufficient adhesion between the matrix and the fiber cause disadvantages. To overcome these issues, in this experimental study, two leaf-based plant fibers are hybridized and the composites have been fabricated by hand lay-up process. The composites were subjected to several tests. The results showed that the hybridization of sisal and pineapple leaf fiber (PALF) increases the mechanical strength of the composite by a maximum tensile strength of 3.59 kN, a little lower flexural strength than the individual fiber, and a noticeably higher compressive strength. The results further showed that the decreased affinities for moisture content and the aged composites seem to be prone to be hydrophilic. Findings of the experiments reveal that the hybridization of sisal and PALF has a significant influence on the properties of the composites. The scanning electron microscopy micrographs of fractured surfaces have been examined, and the findings have effectively been investigated.